Cloning and characterization of a UV-B-inducible maize flavonol synthase - Falcone Ferreyra, María Lorena (2010)
Flavonols are important compounds for male fertility in maize and other crops, and they also contribute to protecting plants from UV-B radiation. However, little continues to be known on how maize and other grasses synthesize flavonols, and how flavonol biosynthesis is regulated. By homology to an Arabidopsis flavonol synthase (FLS1), we cloned a maize gene encoding a product (ZmFLS1) capable of converting the dihydrokaempferol (DHK) and dihydroquercetin (DHQ) dihydroflavonols to the corresponding flavonols, kaempferol (K) and quercetin (Q). Moreover, ZmFLS1 partially complements the flavonol deficiency of Arabidopsis fls1 mutant and restores anthocyanin accumulation to normal levels. We demonstrate that ZmFLS1 is under the control of the anthocyanin (C1/PL1 + R/B) and 3-deoxy flavonoid (P1) transcriptional regulators. Indeed, using chromatin immunoprecipitation (ChIP) experiments, we demonstrate that ZmFLS1 is an immediate direct target of the P1 and C1/R regulatory complexes, revealing a similar control as for earlier steps in the maize flavonoid pathway. Highlighting the importance of flavonols in UV-B protection, we also show that ZmFLS1 is induced in maize seedlings by UV-B, and that this induction is in part mediated by the increased expression of the P1, B and PL1 regulators. Together, our results identify a key flavonoid biosynthetic enzyme so far missed in maize and other monocots, and illustrate mechanisms by which flavonol accumulation is controlled in maize.